O direito à convivência familiar e comunitária de crianças e adolescentes vítimas de abuso sexual intrafamiliar: análise de processos judiciais - Sousa, Débora Tomé de (2019)
The study will address the relevant issue of the right to family and community coexistence of children and adolescents victims of intrafamily sexual abuse. The Federal Constitution of 1988, when adopted the doctrine of integral protection, recognized several fundamental rights of children and adolescents. One of these rights is the one to family and community coexistence, which corresponds to the right of such individuals to grow up and be educated in the family environment with love, affection, mutual respect and protection, as well as to participate actively in the society and community in which they live, with access to recreation, religious, cultural and other activities. In this context, it can be seen that, despite being the ideal place for the full development of individuals, especially children and adolescents because they are in formation, the family may violate their fundamental rights as in the case of intrafamily sexual abuse. That being said, to conceptualize intrafamily sexual abuse as any and all libidinous act or carnal conjunction practiced by a family person, who is in a higher degree of maturity and development than the child or adolescent against them. In cases of abuse, a number of protection measures can be determined aiming at safeguarding children and adolescents who are victims, such as the removal of the abuser from the home, placement of the victim in an extended or welcoming family, or, in the last case, placement in the host institution. However, it was verified through readings on the subject that the protective measure of placement in institutional reception was being determined even without prior study on the possibility of determining another less burdensome measure the right to family and community coexistence of victims, and that they spent a lot of time in institutional. Thus, the general objective of the study is to analyze how the Children and Youth Court of the Region of Fortaleza promote the fundamental right to family and community coexistence of children and adolescents, victims of intrafamily sexual abuse, so that they can have their full and healthy development. The methodology used was based on a descriptive-analytical study, developed through a bibliographical research based on scholars such as Ângela de Alencar Araripe Pinheiro, as well as the Brazilian legislation, jurisprudence and specialized publications. Furthermore, field research was also used, with the analysis of court lawsuits of institutional protection measures, in which the children or adolescents involved were accepted as a result of intrafamily sexual abuse, which are processed in the Children's Court and of the Youth of the Region of Fortaleza. It was verified with the field study that the maximum deadline imposed by the legislation for the institutional reception is not respected, since children and adolescents spend a lot of time in the shelters until their situations are resolved by the Judiciary, a fact that violates their rights to family and community coexistence, as well as that there should be a greater commitment on institutional strengthening in the strengthening of family ties and more efficient public policies for restructuring and assistance to the families of the victims, so that it can increase the percentage of children returning and adolescents welcomed to their families of origin.